Bias in Peer Assessment: Challenges, Solutions, and Best Practices for Fair Student Evaluation - Mohammad Ridwan; Ahmad Najib; Hasan Ruzakki; Rofiqi Rofiqi; Muslimin Muslimin (STAI Hubbulwathan Duri, 2025)
Bias in student evaluations is a persistent challenge in peer assessment, often leading to inaccurate or unfair outcomes. This study investigates strategies to minimize bias and enhance the objectivity and reliability of peer assessment practices in educational settings. A Systematic Literature Review (SLR) was conducted, analyzing 53 peer-reviewed journal articles published between 2019 and 2023. Articles were sourced using the Publish or Perish application, which extracts data from Google Scholar, selected for its extensive coverage of open-access academic sources. Inclusion criteria focused on article quality, thematic relevance to bias in peer assessment, and novelty of insights. Key databases such as Scopus and Web of Science were used to validate and cross-check influential studies. The review identified several effective strategies for minimizing bias in peer assessment. These include maintaining student anonymity, using structured rubrics, providing evaluative training, and incorporating teacher supervision. Each approach demonstrated significant improvements in the fairness and accuracy of assessments across diverse educational contexts. Compared to previous literature, this study offers a more comprehensive synthesis of bias-reduction techniques and emphasizes their practical applicability. By adopting these strategies, educators can improve the validity of peer feedback, fostering more equitable assessment environments and promoting student growth through reflective learning.